Engaging Vocational Students’ Self-efficacy in Reading Comprehension through Literature Circle - Putri Kharisma Wati; Elih Sutisna Yanto (Universitas Majalengka, 2022)
Many students still struggle to comprehend the text in the context of reading comprehension. Students lack motivation because they lack confidence in their reading comprehension abilities. Students are not engaged when they are not ambitious to read. Learning does not occur in this state. Although many previous studies have investigated the correlation between self-efficacy and reading comprehension, the application of reading strategies, in general, to assess students' self-efficacy is deemed less effective because students in Indonesia are unfamiliar with reading English, particularly reading comprehension. To fill the research gap previously identified, this study will examine the self-efficacy of vocational students in reading comprehension using Literature Circle as a reading strategy. The classroom action design was used in this study with fifteen vocational students. Data from a self-efficacy questionnaire and an interview were collected and analyzed using descriptive statistics. According to the findings of this study, the literature circle in this study helps students improve their self-efficacy and achieve aspects of reading comprehension assessment.